Clinical Practice Guidelines for Herniated Disk Treatment - José Ramón Tejera del Valle; Joaquín Aguilar Trujillo; Danny Barrueta Reyes; José Gómez Cruz; Líder Tejera Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Herniated Disk Treatment. The current concept is not only limited to the disorder caused by the rupture of the intervertebral disk, it also includes primary disk degeneration and the resulting spondylosis, and disk disorders associated with this degeneration, traumas and aseptic and granulomatous discitis. Concept, diagnosis, treatment and aetiology are defined and commented stressing the neurosurgical aspects. It includes assessment guidelines focused on the most important aspects to be accomplished.